Development of Robotic Arm and Control System via Smartphone with Multi-Axis Linear Motion Control Techniques - Heamawatanachai, Sumet; Mayang, Supap (Naresuan University Engineering Journal, 2021)
This paper is a design and development of a 6-axis robot arm that can pick up small objects, such as pill boxes and TV remotes, etc. The robot arm is controlled by an application on a smartphone via Bluetooth and Wi-Fi and can show images from the camera attached to the arm on the phone’s screen in real-time. The theory of forward and inverse kinematics was applied to analyze the appropriate working area of the robot arm. In order to make the system suitable for control via a smartphone’s screen, the software in this research was developed to be able to control multiple servo motors simultaneously to move the gripper of the robot arm linearly, forwards-backwards (+x, -x) and in up-down directions (+y, -y). There were two main experiments to evaluate the performance of the system. The first was to test the movement ability of the arm, and the results showed that it was able to move within the specified working area. The second examined the amount of time spent manipulating the robot arm to pick up objects. From the result of this experiment, it was found that the multi-axis linear motion control technique developed in this research, was approximately 86% less time consuming than the independent single-joint control technique